The Social Impact of Fiscal Policy: A Comparative Analysis of Public Investment and Taxation on Social Welfare in Albania (2000-2023) - Hykaj, Ardita; Angjeli, Anastas (European Journal of Social Science Education and Research, 2025)
Fiscal policy is a critical instrument for shaping not only economic trajectories but also social outcomes. This study empirically assesses the comparative impact of public investment and tax revenues on social welfare, proxied by economic growth, in Albania from 2000 to 2023. By dividing the analysis into pre-crisis (2000–2007) and post-crisis (2008–2023) periods, this paper provides evidence-based insights into the shifting effectiveness of fiscal instruments in fostering an economic environment conducive to social development. Using an Ordinary Least Squares (OLS) regression framework with minimalist and lagged models, the study analyzes annual time-series data. A suite of econometric diagnostics, including tests for stationarity (ADF), multicollinearity (VIF), heteroscedasticity (White), autocorrelation (Durbin-Watson), and normality of residuals (Jarque-Bera), ensures the robustness of the findings. The results reveal a structural shift in fiscal policy effectiveness. In the pre-crisis period, public investment, particularly with a one-year lag, was a significant driver of growth, suggesting its role in building foundational infrastructure with broad social benefits. Conversely, in the post-crisis era, tax revenues emerged as a statistically significant growth-enhancing factor, reflecting improved fiscal capacity to fund social programs and ensure stability. The impact of public investment, while still positive, diminished in significance, raising questions about its efficiency and allocation towards socially impactful projects. This research contributes to the social science literature by contextualizing the economic impact of fiscal levers within a broader social welfare framework, offering critical insights for policymakers in transition economies on how to balance growth-oriented policies with objectives of social equity and sustainable development.